La familia en el comportamiento de los jóvenes con deficiencia intelectual leve de 15-18 años que asisten al Centro de Rehabilitación Sendero de Alegría de la ciudad de Loja, periodo 2013- 2014 - Sánchez Tapia, Tatiana Maribel (2015)
The purpose of the research was to understand how the family influences the behavior of young people with mild intellectual disability 15-18 years who attend the rehabilitation center “Path to Joy" from the city of Loja, 2013- 2014 period. The methods used were: scientific method, analytic- synthetic method, deductive method and statistical method; was used as techniques and instruments: the survey of staff, functional Educational Styles questionnaire applied to parents of middle and observation sheet applied to young people. The research population consisted of 90 students, 90 representatives and 7 professionals working in the institution, it was sampled 10 young people with mild intellectual disabilities between the ages of 15-18, 10 parents and 7 professionals doing A total of 27 persons investigated. It was determined that parents have the permissive parenting style and who do not exercise any control over their children , their level of demand is very low , accepting their behavior as there are no standards or rules at home , young manifest the passive behavior by interacting with peers are uncommunicative , expressing fears. It is recommended that the institution conducting workshops to train parents on parenting style to get a better result in the rehabilitation of the young.